Analisis Ibuprofen Pada Sediaan Jamu Pegal Linu Berdasarkan Beberapa Penelitian Menggunakan Metode Kromatografi Lapis Tipis: Literature Review - Dhea Mutiara; Aledea Safitri; Anggel Imelda Ranboki; Firdha Senja Maelaningsih (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Ibuprofen is one of the nonsteroidal anti-inflammatory drugs (NSAIDs) used to reduce fever and alleviate pain. However, when used over an extended period, ibuprofen can pose serious health risks. Possible side effects include the risk of developing gastric ulcers, kidney dysfunction, and liver problems. The Indonesian government, through Regulation of the Minister of Health of the Republic of Indonesia No. 007 of 2012 on the registration of traditional medicines, has prohibited traditional medicines from containing pharmaceutical chemical substances. The objective of several studies conducted is to identify the presence of chemical substances, in this case, ibuprofen, in traditional herbal remedies for muscle pain relief. In the identification process, the technique used is Thin Layer Chromatography (TLC) using silica gel GF254 as a buffer. The mobile fraction used consists of a mixture of ethyl acetate, methanol and ammonia, and detection under UV light with a wavelength of 254 nm. The results showed a 3 out of 5 result regions conducting research identified the presence of ibuprofen in herbal remedies for muscle pain relief. Banjarmasin, Magelang, and Purwokerto are the regions where ibuprofen was detected in these herbal remedies.